Study of dough fermentation process with flax seeds - Bondarenko, Yuliia; Andronovich, Galina; Kaprelyants, Leonid; Bilyk, Olena; Naumenko, Oksana (My University, 2023)
The article investigates the fermentation processes in wheat dough containing whole and crushed flax seeds in dry and soaked states. It was found that in the process of fermentation in samples with whole flax seeds in dry and moistened states, the amount of carbon dioxide released slightly increases compared to the control. In the samples with crushed flax seeds in dry form and with moistened crushed flax seeds, the total amount of carbon dioxide released is higher than in the control sample by 16.5 % and 19.0 %, respectively. In the sample with crushed flax seeds, the nature of the dynamics of carbon dioxide release differs from the control sample, namely, a one-stage fermentation is observed. At the same time, the peak of carbon dioxide emission was observed almost 30 minutes later than in the control sample. The use of moistened whole and crushed flaxseeds results in a slightly lower intensity of carbon dioxide emission compared to dry samples. Based on the analysis of the dynamics of carbon dioxide emission, it is recommended to reduce the duration of dough fermentation for the sample with whole flax seeds to 90 minutes, and for the samples with crushed seeds and soaked flax products to 60 minutes. It was found that the introduction of whole and crushed flax seeds in a moistened form slows down the rise of the dough due to the thickening of the dough system with water-soluble and insoluble flax dietary fiber, reducing fermentation and the formation of sugars in the dough system.

У статті досліджено процеси бродіння в пшеничному тісті, в яке було внесено ціле та подрібнене насіння льону в сухому та замоченому станах. Встановлено, що в процесі бродіння у зразках з цілим насінням льону у сухому та зволоженому станах кількість виділеного діоксиду вуглецю незначно зростає, порівняно з контролем. У зразках з подрібненим насінням льону у сухому вигляді та зі зволоженим подрібненим насінням льону загальна кількість виділеного вуглекислого газу вища, ніж у контрольному зразку на 16,5 % та 19,0 % відповідно. У зразку з подрібненим насінням льону характер динаміки виділення діоксиду вуглецю відмінний від контрольного зразку, а саме спостерігається одностадійність бродіння. При цьому досягнення піку виділення вуглекислого газу відзначається майже на 30 хв пізніше, ніж в контрольному зразку. Застосування зволоженого цілого та подрібненого насіння льону зумовлює дещо нижчу інтенсивність виділення вуглекислого газу, поряд із сухими зразками. На підставі аналізу динаміки виділення вуглекислого газу, рекомендовано скоротити тривалість бродіння тіста для зразку з цілим насінням льону до 90 хв, а для зразків з подрібненим насінням та замоченими лляними продуктами до 60 хв. Встановлено, що внесення цілого та подрібненого насіння льону в зволоженому вигляді зумовлює уповільнення підйому тіста внаслідок загущення тістової системи водорозчинними та нерозчинними харчовими волокнами льону, зниження зброджування та утворення цукрів в тістовій системі.
Keywords: dough; fermentation; whole flax seeds; crushed flax seeds; yeast; flax seed polysaccharides; кафедра технології хлібопекарських і кондитерських виробів; тісто; бродіння; ціле насіння льону; подрібнене насіння льону; дріжджі; полісахариди насіння льону